Structural damage detection in an aeronautical panel using analysis of variance - Gonsalez, Camila Gianini [UNESP]; Silva, Samuel da [UNESP]; Brennan, Michael J. [UNESP]; Lopes Junior, Vicente [UNESP] (Elsevier B.V., 2015)
This paper describes a procedure for structural health assessment based on one-way analysis of variance (ANOVA) together with Tukey's multiple comparison test, to determine whether the results are statistically significant. The feature indices are obtained from electromechanical impedance measurements using piezoceramic sensor/actuator patches bonded to the structure. Compared to the classical approach based on a simple change of the observed signals, using for example root mean square responses, the decision procedure in this paper involves a rigorous statistical test. Experimental tests were carried out on an aeronautical panel in the laboratory to validate the approach. In order to include uncontrolled variability in the dynamic responses, the measurements were taken over several days in different environmental conditions using all eight sensor/actuator patches. The damage was simulated by controlling the tightness and looseness of the bolts and was correctly diagnosed. The paper discusses the strengths and weakness of the approach in light of the experimental results. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Structural health monitoring; Electromechanical impedance; ANOVA; Multiple comparison procedures